Assessment of Insecticide Resistance in Spodoptera litura (Fabricius) in Vegetable Crop Ecosystem - Sowmya K; Sunitha Devi R; Rajanikanth, P; Rajeswari, B (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
One of the most prevalent insect pests is the tobacco caterpillar or Spodoptera litura (Fabricius), which results in significant crop losses developed resistance against different insecticides over time. This laboratory experiment was carried out in the Department of Entomology, College of Agriculture, Rajendranagar, Professor Jayashankar Telangana State Agricultural University (PJTSAU), Hyderabad during Karif, 2022. The susceptible population was reared in laboratory continuously for ten generation without exposing it to insecticides. The susceptibility of field populations of S. litura that were collected from many vegetable crops in the intense vegetable crop cultivating mandals i.e., Chevella and Maheshwaram of Rangareddy district to commonly used insecticides viz., chlorantraniliprole, emamectin benzoate and flubendamide was then compared with a laboratory reared susceptible population The bioassay studies revealed that the LC50 values of these insecticides were significantly higher in the field population collected from Chevella and Maheshwaram compared to the susceptible laboratory population. Based on the LC50 values the Resistant ratio (RR) was calculated for the field populations. It was found that Chevella population developed 35.34 folds resistance and Maheshwaram population also developed nearly 34.90-fold resistance against emamectin benzoate. Both Chevella and Maheshwaram populations were found to develop moderate resistance of 28.23 and 27.35-fold against flubendamide and comparatively lower resistance of 21.05 and 23.44-fold resistance against chlorantraniliprole when compared to susceptible population. These findings further helps in developing better IRM strategies.